2020
DOI: 10.18690/rei.13.1.73-87.2020
|View full text |Cite
|
Sign up to set email alerts
|

The impact of online learning on student motivation in science and biology classes

Abstract: The research aimed to check for difference in learning motivation between students learning online and students participating in modern classroom instruction. The study participants included students attending grades 5 to 8, divided into experimental (online classes) and control groups based on pre-testing. The results show that there is no statistically significant difference in motivation between the tested sub-samples. Student motivation for learning natural sciences declines with their years of schooling, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 12 publications
1
9
0
3
Order By: Relevance
“…Keraro et al (2007) advocated that students showed a high motivation toward learning biology after being treated by cooperative concept mapping teaching approach, while in the study by Özarslan and Çetin (2018), biology projects proved negative effect on students" motivation toward learning biology. Online teaching did not display a significant difference in improving student motivation toward learning biology in comparison to traditional instructional methods (Bulic & Blazevic, 2020). Hence, it is imperative to test the motivational level in pre-service biology teachers' after being treated by animation-based instructions and small-group laboratory activities.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Keraro et al (2007) advocated that students showed a high motivation toward learning biology after being treated by cooperative concept mapping teaching approach, while in the study by Özarslan and Çetin (2018), biology projects proved negative effect on students" motivation toward learning biology. Online teaching did not display a significant difference in improving student motivation toward learning biology in comparison to traditional instructional methods (Bulic & Blazevic, 2020). Hence, it is imperative to test the motivational level in pre-service biology teachers' after being treated by animation-based instructions and small-group laboratory activities.…”
Section: Introductionmentioning
confidence: 93%
“…In general, studies by Dohn et al (2016), Mnguni (2018), Özbaş (2019), and Kişoğlu (2018) were interested in finding out the students motivation toward learning biology; however, the literature lacks sufficient studies on pre-service biology teachers motivation toward learning biology. Besides, the effect of different instructional methods on student's motivation toward learning biology was found out (Bulic & Blazevic, 2020;Corkin et al, 2017;Dyrberg et al, 2017;Hewitt et al, 2019;Keraro et al, 2007;Özarslan & Çetin, 2018), but minor studies focused on the effect of resourcebased instructions on pre-service biology teacher's motivation toward learning biology. Likewise, a recent study done in higher learning institutions in Rwanda (Mukagihana et al, 2020) showed low use of resource-based instructional tools prevailed to teach and learn biology.…”
Section: Introductionmentioning
confidence: 99%
“…This was done on 162 primary school students. It showed that there was no significant difference in student's motivation (Bulić & Blažević, 2020). This is however contrasted by Lee (2000), who points out the high student dropout rates of online courses.…”
Section: Student Motivation In the Online Environmentmentioning
confidence: 86%
“…A study by Bulić and Blažević (2020) focused on levels of student motivation in the online environment in comparison to modern classroom instruction. This was done on 162 primary school students.…”
Section: Student Motivation In the Online Environmentmentioning
confidence: 99%
“…Selanjutnya penyampaian materi kuliah yang tidak sejelas perkuliahan offline, keperluan internet yang besar, dan kondisi jaringan atau sinyal internet yang tidak stabil sehingga membuat perkuliahan daring menjadi kurang efektif (Herliandry et al, 2020). Beberapa siswa juga mengeluh dengan materi yang disampaikan oleh guru (Bulic & Blazevic, 2020). Selain itu, dampak lain yang dapat dirasakan oleh peserta didik dari pembelajaran secara daring adalah pelajaran yang terlalu berlimpah yang menekan siswa atau peserta didik untuk bisa mengikuti pelajaran dengan telaten dan hati-hati.…”
Section: Pendahuluanunclassified